Study on Acoustic Emission Characteristics and Mechanical Behavior of Water-Saturated Coal - Muhammad Ali; Enyuan Wang; Zhonghui Li; Haishan Jia; Dexing Li; Izhar Mithal Jiskani; Barkat Ullah (Geofluids)
In terms of coal’s stability and failure, soaking time and water content play a significant role in geotechnical engineering practice. To determine the soaking time effect on the mechanical behavior of coal samples and the response of AE (acoustic emission) signal throughout loading, the samples with different soaking times (0–120 hours (h)) were prepared and tested under uniaxial compression. AE signals were continuously monitored during loading to examine the AE characteristic response via the AEwin Express-8.0 system. The results revealed that the mechanical characteristics of the coal samples decreased with an increase in soaking time. When coal samples were subjected to uniaxial compression, AE events occurred due to the formation of the cracks, which further propagated to cause coal fracture. AE counts and the accumulative counts fluctuated with time and corresponded very well to the load. Therefore, AE counts and the trend of the accumulative counts of AE qualitatively explained the rupture of the coal under stress. In addition, the variation in trends of AE counts, AE accumulative counts, and load with time at various phases of all samples were obtained. It is concluded that AE counts increase suddenly during a slow increase phase and peak at the active increase phase. During the attenuation phase, the AE counts first decrease significantly with stress drop, but also a slight increase was observed due to the initiation of secondary cracks. These research results are of great significance as a precursor in coal and rock failure.